Formal total synthesis of (±)-7-deoxycylindrospermopsin and its 8-epi isomer. Issue 13 (27th April 2021) - Wang, Si-Qing; Qi, Wei-Yi; Yin, Xue-Song; Shi, Bing-Feng
Abstract : A concise formal synthesis of (±)-7-deoxycylindrospermopsin in 14 steps was reported. Abstract : 7-Deoxycylindrospermopsin is a member of cylindrospermopsin marine alkaloid containing a cyclic guanidine group. Herein, we present a concise formal total synthesis of (±)-7-deoxycylindrospermopsin in 14 steps from commercailly available 4-methoxypyridine. Key features of our synthetic route include the elaboration of densely functionalized piperidine via 1, 4-addition of propargylindium to enone, Sonogashira coupling to attach the pyrimidine moiety, and intramolecular conjugate addition of guanidine with alkyne to form C ring. The synthesis of its 8- epi isomer was also achieved following the same synthetic strategy.